The Status of Copyright as Jointly Acquired Property According to the Syariah Perspective: (Status hak cipta menurut perspektif perundangan syariah) (Kanun: Jurnal Undang-undang Malaysia, 2022)
The provisions of Islamic Family Law state that any asset acquired during the period of marriage can be claimed as jointly acquired property. However the status of copyright as jointly acquired property is still debatable. The objective of this study is to study the concept of copyright as jointly acquired property according to the perspective of Shariah law and to analyze copyright as jointly acquired property according to the opinion of Shariah practitioners and the experts. The research framework is qualitative study, applys document analysis design and semi-structured interviews. The data were obtained through the statutes of copyright and jointly acquired property in Malaysia, the fiqh of the four sunni schools as well as interviews of Shariah legal practitioners, copyright law experts and religious scholars. The findings of this study found that Islam also recognizes copyright in jointly acquired. It also can be recognised as intangible property that can be claimed as jointly acquired property if it is owned during the marriage or developed during the marriage, by looking at the contribution factors of husband and wife in acquiring the property. The results of the interviews also showed that the informants supported the theory of copyright as jointly acquired property. The research implication contributes in the study of Shariah knowledge and can be referred by the syariah and civil courts in dealing with the issue of copyright as jointly acquired property. This study also proposes to the legislators to enact the laws that related to copyright and jointly acquired property, regarding property that can be claimed as jointly acquired property.Keywords: Legislation, Sharia, marriage, jointly acquired property, copyright, intangible propertyFull text: PDF